Israel : Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Israel. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that Israel's economy has been doing well and near-term growth prospects are favorable. Following growth of 2.6 percent in 2014, the economy is expected to expand by about 2.5 percent in 2015 and 3-3.3 percent each year in the medium term. Employment creation has been remarkable-growing by 3.5 percent annually-and unemployment is at multi-decade lows. Inflation has been negative, but this trend reflects temporary external factors, not domestic weakness. Debt has declined to 67 percent of GDP from a peak of 94 percent of GDP in 2003 but is expected to increase for the first time since 2009, following the upward revisions to the deficit targets.